Pengaruh Profitabilitas, Tata Kelola Perusahaan Dan Penghindaran Pajak terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020 - Rika Mei Hayani Ginting; Rosanna Purba; Renika Hasibuan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
This study aims to determine whether profitability, corporate governance and tax avoidance affect the firm value of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020 partially and simultaneously. The population in this study were 147 companies. The sampling method used was purposive sampling method, so that 38 companies were obtained as samples for 4 years of observation with 152 samples of observations. The research data were obtained from the annual financial reports of the sample companies which were downloaded via the IDX website, namely www.idx.co.id and the official websites of each company. The data analysis technique used is multiple linear regression analysis using SPSS 17. Based on the results of the study, it shows that profitability, independent board of commissioners, managerial ownership have an effect on firm value partially, and tax avoidance has no effect on firm value partially and profitability, independent board of commissioners , managerial ownership and tax avoidance affect firm value simultaneously.